New Approaches for Harmonic Reduction Using Cascaded H-Bridge and Level Modules - Prof. P.K.Sankala; K.N.Nandargi (International Journal of Innovations in Engineering Research and Technology, 2021)
This paperanalyzes and compares two approaches fordc to ac power conversion i.e. inverter. First methoduses cascaded H-BridgeInverter and second uses new Multi-level Scheme having LevelModules and H-Bridge. Thesimulation is done inMATLAB Software.Also the hardware can bedone by taking the AC supply from the mains and converts it into DC supply by using rectifier. MOSFET can be used for switching purpose.The Total Harmonic Distortion in output loadvoltage, produced by both theapproaches is compared